Gender Justice in Islamic Education (A review of the book Al-Adala al-Ijtima'iyya fi'l-Islam by Sayyid Qutub) - Asep Awaluddin; Anip Dwi Saputro; Syamsul Arifin (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
The problem of gender justice in Islamic education starts from history and is still visible on the outside in our Islamic educational institutions. It was only in the 20th century that women obtained equal rights in education, although this equality had not been fully marked by the leaders of educational institutions in general, which were men. This research is a descriptive qualitative research with library-based data collection. The results of this study indicate that there is a need for gender equality reformulation in the leadership of Islamic educational institutions so that they can be more advanced and have high competitiveness, namely by utilizing a leadership model that includes women as part of the leadership board, namely 1) forming a board of directors. leaders of educational institutions by paying attention to gender participation, 2) increasing the facilitation of Islamic educational institutions for women, including sports and skills facilities.